2016
DOI: 10.5781/jwj.2016.34.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Hardness of Surface Melting Hardened Zone of Mold Steel, SM45C using Yb:YAG Disk Laser

Abstract: This study applied laser surface melting process using CW(Continuous wave) Yb:YAG laser and cold-work die steel SM45C and investigated microstructure and hardness. Laser beam speed, power and beam interval are fixed at 70 mm/sec, 2.8 kW and 800 ㎛ respectively. Depth of Hardening layer(Melting zone) was a minimum of 0.8 mm and a maximum of 1.0 mm that exceeds the limit of minimum depth 0.5 mm applying trimming die. In all weld zone, macrostructure was dendrite structure. At the dendrite boundary, Mn, Al, S and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, when the laser scan speed was increased by 300 to 500 mm, both alloy depth alloy widths were decreased [35]. The effect of the beam diameter was also observed in [36,37], where there is an optimum beam diameter for the best performance. During laser alloying, the phenomena occurring are slightly more complicated due to the input of additional elements or compounds to the substrate material with other laser parameters.…”
Section: Introductionmentioning
confidence: 56%
“…Similarly, when the laser scan speed was increased by 300 to 500 mm, both alloy depth alloy widths were decreased [35]. The effect of the beam diameter was also observed in [36,37], where there is an optimum beam diameter for the best performance. During laser alloying, the phenomena occurring are slightly more complicated due to the input of additional elements or compounds to the substrate material with other laser parameters.…”
Section: Introductionmentioning
confidence: 56%
“…Appropriate surface treatments can prevent damages to the mold, resulting in an extended mold lifespan. Several studies have investigated the application of surface treatments to mold steels and tool steels in the form of surface heat-treatment [2][3][4][5], nitriding [3,[6][7][8], surface coating and alloying [9][10][11][12], and peening [5,13,14]. Lee et al [2] investigated the laser melting-induced microstructural evolution and surface hardening of SM45C mold steel.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the application of surface treatments to mold steels and tool steels in the form of surface heat-treatment [2][3][4][5], nitriding [3,[6][7][8], surface coating and alloying [9][10][11][12], and peening [5,13,14]. Lee et al [2] investigated the laser melting-induced microstructural evolution and surface hardening of SM45C mold steel. Telasang et al [4] reported that laser surface hardening/melting improved the wear and corrosion resistances of AISI H13 tool steel.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous available manufacturing processes, laser-beam-assisted processes are particularly versatile because of their diverse application range and superior manufacturing efficiency, including welding [6][7][8], cladding [9], surface alloying [10,11], selective melting [12][13][14], shock peening [15,16], and riveting [17]. Selective control of surface material properties is also possible through laser processing.…”
Section: Introductionmentioning
confidence: 99%